Estudo do Léxico policial militar - Paulo César Ribeiro Nunes (2012)
The Work entitled Estudo do Léxico Policial Militar (LPM), has as initial goal the description of the lexicon in use by the military police, in order to observe the changes in the period extending from 1964 until the present day. It should be noted that the Polícia Militar de Minas Gerais (PMMG) acts in all the cities of Minas Gerais but, for the reasonableness of the developed research, it was taken as target only employees of that institution who worked and work in Belo Horizonte, in to the following periods: historical moments ranging from the 1964 Revolution until the promulgation of the 1988 Constitution, the 90's and the present day. The analysis verified the role of age as an extra linguistic factor: the subjects were divided into three age groups - 20 to 25 years, 30 to 40 years and 45 to 60 years old. To obtain the data, it was applied a questionnaire with multiple and discursive answers related to police use of objects and everyday situations. The lexical units (LU) in the answers were analyzed based on the use frequency, what determined the classification of words and/ or expressions in groups more stable, less stable and unstable. The quantitative analysis showed the performance of the younger age group in the replacement process of numerous items. In addition, the quantitative analysis allowed establishing that the fostering of this parameter is related to others, such as historical, ideological and functional factors.